2006
DOI: 10.1111/j.1462-2920.2006.01134.x
|View full text |Cite|
|
Sign up to set email alerts
|

217 000‐year‐old DNA sequences of green sulfur bacteria in Mediterranean sapropels and their implications for the reconstruction of the paleoenvironment

Abstract: Summary Deep‐sea sediments of the eastern Mediterranean harbour a series of dark, organic carbon‐rich layers, so‐called sapropels. Within these layers, the carotenoid isorenieratene was detected. Since it is specific for the obligately anaerobic phototrophic green sulfur bacteria, the presence of isorenieratene may suggest that extended water column anoxia occurred in the ancient Mediterranean Sea during periods of sapropel formation. Only three carotenoids (isorenieratene, β‐isorenieratene and chlorobactene) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(127 citation statements)
references
References 48 publications
4
122
1
Order By: Relevance
“…The diversity of microbial life will be quantified and compared with geological and geochemical data to answer questions such as was the microbiology shaped by the post-impact hydrothermal system, and did organic matter get trapped within hydrothermal minerals? The deep biosphere will be investigated using culturing, molecular biological analyses of DNA, searching for biosignatures such as hopanoids and other lipids/biomolecules, and paired analyses of paleome (the genome of an extinct species) and lipid biomarkers (Cockell et al, 2005;Coolen and Overmann, 2007;Coolen et al, 2013). Iron isotopes will also be used to detect biosignatures because they are particularly useful for studies of ancient, severely metamorphosed and/or altered rocks (Yamaguchi et al, 2005).…”
Section: Deep Biosphere and Habitabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The diversity of microbial life will be quantified and compared with geological and geochemical data to answer questions such as was the microbiology shaped by the post-impact hydrothermal system, and did organic matter get trapped within hydrothermal minerals? The deep biosphere will be investigated using culturing, molecular biological analyses of DNA, searching for biosignatures such as hopanoids and other lipids/biomolecules, and paired analyses of paleome (the genome of an extinct species) and lipid biomarkers (Cockell et al, 2005;Coolen and Overmann, 2007;Coolen et al, 2013). Iron isotopes will also be used to detect biosignatures because they are particularly useful for studies of ancient, severely metamorphosed and/or altered rocks (Yamaguchi et al, 2005).…”
Section: Deep Biosphere and Habitabilitymentioning
confidence: 99%
“…Study of biomarkers at the molecular level (high-pressure liquid chromatography [HPLC] and liquid chromatography-mass spectrometry [LC-MS]) and pigments (chlorophylls, bacteriochlorophylls, and their degradation products) from photosynthetic organisms (algae and photosynthetic bacteria) may indicate changes in and evolution of photosynthetic organism populations after impact. It is expected that both marine and terrestrial organic matter have accumulated in the post-impact sedimentary rock and that the paired stratigraphic analysis of the paleome and lipid biomarkers and their isotopic compositions using precisely dated core material will provide detailed insights into post-impact environmental conditions and the recovery and evolution of surface and deep subsurface life (Coolen et al, 2007(Coolen et al, , 2013. Of interest is the ocean chemistry and temperature immediately following the impact and any indicators of climatic recovery.…”
Section: Recovery Of Lifementioning
confidence: 99%
“…In marine sediments, the presence of eDNA sequences has been reported from organic-rich layers in the Mediterranean dating back to 217 ka (Coolen and Overmann, 2007) and 125 ka (Boere et al, 2011), in sediments covering the last 11.4 kyr in the Black Sea (Coolen et al, 2013), and in up to 32.5 kyr old deposits in the Atlantic (Lejzerowicz et al, 2013;Pawłowska et al, 2014). Recently, Kirkpatrick et al (2016) showed that the abundance of planktonic DNA was decreasing within 100-200 ka in sediments of the Bering Sea but traces were still detected in sediments up to 1.4 Ma.…”
Section: Introductionmentioning
confidence: 99%
“…The current state of knowledge is that ancient planktic DNA can be recovered from sediments as old as 270,000 y and successfully used for ecosystem reconstructions (Coolen and Overmann, 2007;Randlett et al, 2014). The majority of DNA in the marine sedimentary record was reported to be extracellular (Corinaldesi et al, 2008) and protected against microbial enzymatic attack through mineral adsorption.…”
Section: Ancient Biospherementioning
confidence: 99%